Free Cash Flow, Agency Theory Dan Signaling Theory: Konsep dan Riset Empiris - Abdullah, Syukriy (Universitas Muhammadiyah Yogyakarta, Indonesia, 2002)
This paper discusses the literature on free cash flow (FCF), which is one source of corporate funding that can be distributed to investors after finance all investments with positive NPV. FCF contain agency problems (Jensen, 1986) giving rise to agency costs such as auditing fees. FCF can be distributed through dividends or stock repurchase, but sometimes management does not do so and instead uses for wealth management, such as for bonus and investment that can increase power and reduce the possibility of takeover. FCF can be used by management as a signal about the prospects of the company in the future due to policies such as specially designated dividend and stock repurchase has information content. In addition, some studies suggest that the management policy on FCF correlated with income and dividends smoothing.